The effect of service quality, tourist satisfaction, place attachment on environmentally responsible behavior in Praiijing traditional village - Yoanna Evangeline; Siti Rahayu; Adi Tedjakusuma (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to find out and analyze the influence of Service Quality, Tourist Satisfaction, Place Attachment, and Environmentally Responsible Behavior on tourist attractions in Praiijing Traditional Village. Data processing is carried out using quantitative approaches and this type of research is causal. Variables used in this study are service quality, tourist satisfaction, place attachment, and environmentally responsible behavior. Technical analysis of the data used is Structural Equation Modeling (SEM) by using the SPSS 16.0 for Windows and AMOS version 22. This study used samples in the form of responses from respondents who had visited Praiijing Traditional Village with the number of samples used in the study 150 respondents. The results of this study showed the mutual influence between service quality, tourist satisfaction, place attachment, and environmentally responsible behavior.